Correction: Moreno-Fonseca et al. Postfire Scenarios Shape Dung Beetle Communities in the Orinoquía Riparian Forest–Savannah Transition. Biology 2025, 14, 423 - Carlos Julián Moreno-Fonseca; Jorge Ari Noriega; Walter Garcia-Suabita; Dolors Armenteras-Pascual (Biology)
Jorge Ari Noriega was not included as an author in the original publication [...]